(untitled) (ModaPalavra e-periódico, 2011)
This article aims to provide basis for the increasing necessity of Fashion Branding. Through a comprehensive look into the origins of consumer decisions, guided by brands and the emotional ties they create with their consumers, one finds an alternative to traditional means of communication. Fashion companies should abandon traditional views of consolidating a brand through mere systematization of a visual language and rather concentrate in creating discourses, postures, and material elements that will captivate the consumer.